Proposta de modelo para escolha de tecnologias de tratamento de água em pequenas comunidades do semiárido - Ponte, Fernando Victor Galdino (2011)
The water supply systems in Ceará semiarid are deficient with regard to water quality. The water treatment in communities are not being very efficient, since there is no standardization of water treatment plants in relation to the quality of the raw water that is captured. Therefore, it was developed a simplified model of choice selection of water treatment technologies for small communities, which was developed using Excel 2007, where you can make a correct choice of the treatment plant that will supply water to a location. The model consists of two steps. In the first stage are the criteria for exclusion, since it is a simplified model and parameters such as hardness, chloride, fluoride, among others need to be well analyzed, due to their treatment are not feasible for small rural communities and are not in the model‟s result. The second step is the selection of technologies for water treatment itself, on which selecting the source and its characteristics, the model will be able to bring the best result for an effective treatment. In addition to the model‟s results are the hydraulic design and the plant water treatment plants chosen. The technologies used were the Complete Cycle, the Direct Ascendant Filtration, the Double Filtration and Oxidation followed by rapid Ascendant Filtration. The selection criteria were included by a bibliographic review of established authors in water treatment and the criteria for choosing the technology that removes iron were developed in the pilot plant at ETA GAVIÃO.